A rare acute presentation of intestinal malrotation in the elderly - Adesuyi, Abidemi A.; Situ, Oladele O.; Batta, Cephas S. (International Surgery Journal, 2020)
Intestinal malrotation, a congenital anomaly of the midgut, typically presents in pediatrics age group with the most feared complication of midgut volvulus and its catastrophic sequelae. Midgut volvulus secondary to intestinal malrotation is a rare presentation in adults more so in the elderly. Its rarity portends a diagnostic dilemma for both the surgeon and radiologist. We report a 65-year-old man admitted following a referral with a 12-hour history of acute abdomen with an initial diagnosis of acute pancreatitis but later had laparotomy with intraoperative findings of a midgut volvulus and gangrenous ileal segment secondary to intestinal malrotation. This case emphasizes the importance of early diagnosis to prevent the disastrous complication of this disease. The rarity of this condition portends a formidable diagnostic challenge in adults hence the awareness of its possibility and a high index of suspicion is crucial in diagnosis.